STUDY OF BACTERIAL LYSATE IN THE FIGHT AGAINST ANTIBIOTIC RESISTANCE - Junussova, D.A.; Sadykov , A.M.; Kanafina , M.A.; Sharova , D.E.; Issa , D. (Eurasian Journal of Applied Biotechnology, 2025)
Bacterial lysates are widely used today as immunomodulatory agents that enhance the effectiveness of antibacterial therapy through synergistic interactions with antibiotics. The aim of this study was to evaluate the pharmacological properties of a bacterial lysate obtained from antibiotic-resistant strains of opportunistic microorganisms such as Acinetobacter baumaniі, Klebsiella pneumoniae SCAID PND1-2022 (246), and Pseudomonas aeruginosa SCAID PHRX1-2019 to assess its potential in combating the growing problem of antimicrobial resistance. The study analyzed the properties of the lysate and its effects on the body using in vivo studies at doses of 300.0 and 500.0 mg/kg. No signs of acute toxicity were observed, suggesting that this substance is safe for use. Furthermore, destroyed bacterial cells retain the ability to induce a specific immune response, stimulating immune system activation. Given the inherent resistance of bacterial strains to antibiotics, it can be concluded that the use of bacterial lysate promotes the development of an adaptive immune response directed against highly resistant pathogens, including superbugs.